Postharvest biochemical characteristics and ultrastructure of Coprinus comatus - Yi Peng; Tongling Li; Huaming Jiang; Yunfu Gu; Qiang Chen; Cairong Yang; Wei liang Qi; Song-qing Liu; Xiaoping Zhang (PeerJ, 2020)
Background Coprinus comatus is a novel cultivated edible fungus, hailed as a new preeminent breed of mushroom. However, C. comatus is difficult to keep fresh at room temperature after harvest due to high respiration, browning, self-dissolve and lack of physical protection. Methods In order to extend the shelf life of C. comatus and reduce its loss in storage, changes in quality, biochemical content, cell wall metabolism and ultrastructure of C. comatus (C.c77) under 4 °C and 90% RH storage regimes were investigated in this study. Results The results showed that: (1) After 10 days of storage, mushrooms appeared acutely browning, cap opening and flowing black juice, rendering the mushrooms commercially unacceptable. (2) The activity of SOD, CAT, POD gradually increased, peaked at the day 10, up to 31.62 U g−1 FW, 16.51 U g−1 FW, 0.33 U g−1 FW, respectively. High SOD, CAT, POD activity could be beneficial in protecting cells from ROS-induced injuries, alleviating lipid peroxidation and stabilizing membrane integrity. (3) The activities of chitinase, β-1,3-glucanase were significantly increased. Higher degrees of cell wall degradation observed during storage might be due to those enzymes’ high activities. (4) The fresh C. comatus had dense tissue and every single cell had the number of intracellular organelles which structure can be observed clearly. After 10 d storage, the number of intracellular organelles was declined and the structure was fuzzy, the nucleus disappeared. After 20 d storage, C. comatus’s organization was completely lost, many cells were stacked together and the cell wall was badly damaged.